Design of methodical basis of the system for monitoring of WWER-440 pressure vessel radiation exposure - A. M. Pugach; V. N. Bukanov; E. G. Vasylyeva; O. V. Grytsenko; V. L. Dyemokhin; S. M. Pugach (Ядерна фізика та енергетика)
Main issues of methodical basis of the monitoring system of WWER-440 pressure vessel radiation exposure are formulated. The designed calculational model of reactor facility is presented. Description of the special equipment for carry out of dosimetry measurements at the outer surface and the procedure for some technological tolerances determination are given.